Tabot Ritual in Islamic Law: Philosophical Reflections on Sunni and Shiite Harmonization - Asmara, Musda; Sugeng, Anggoro; Taufik, Mohammad; Harahap, Purnama Hidayah; Kurniawan, Rahadian (Universitas Islam Negeri Jakarta, 2024)
This study aims to analyze the philosophy of the Tabot ritual, commemorating the death of Ḥasan in the fields of Karbala, rooted in the traditions of Shia and Sunni, from the perspective of Islamic law. The Tabot ritual embodies noble Islamic values intertwined with local wisdom and cultural acculturation in Bengkulu society. This study employs a field research approach, collecting data through in-depth interviews and documentation with religious leaders, traditional leaders, community figures, and residents in Bengkulu. The findings reveal that the nine stages of the Tabot ritual—Mengambik Tanah, Duduk Penja, Menjara, Meradai, Arak Penja, Arak Serban, Gam, Arak Gedang, and Tabot Tebuang—are imbued with profound philosophical meanings in line with Islamic principles. These include the value of acculturation in Mengambik Tanah, self-purification in Duduk Penja, the spirit of Islamic brotherhood in Menjara, and self-reflection in Tabot Tebuang. From an Islamic legal perspective, the Tabot ritual illustrates a harmonious adaptation of ritual practices while adhering to respect and coexistence within Islamic teachings. The ritual’s symbolic modifications, such as removing elements deemed offensive to the Companions of the Prophet Muḥammad SAW, reflect a commitment to maintaining Islamic unity. Although originating from a Shiite tradition, the Tabot ritual has been contextualized and accepted broadly, including by Sunni communities, showcasing its alignment with Islamic jurisprudential values. AbstrakPenelitian ini bertujuan untuk menganalisis filosofi Tabot sebagai ritual memperingati wafatnya Ḥasan di padang Karbala yang berakar pada tradisi Syiah dan Sunni dari sudut pandang hukum Islam. Ritual Tabot merupakan perwujudan nilai-nilai luhur Islam yang terjalin dengan kearifan lokal dan akulturasi budaya masyarakat Bengkulu. Penelitian ini menggunakan pendekatan penelitian lapangan, yaitu pengumpulan data melalui wawancara mendalam dan dokumentasi terhadap tokoh agama, tokoh adat, tokoh masyarakat, dan warga di Bengkulu. Hasil penelitian menunjukkan bahwa sembilan tahapan ritual Tabot—Mengambik Tanah, Duduk Penja, Menjara, Meradai, Arak Penja, Arak Serban, Gam, Arak Gedang, dan Tabot Tebuang—memiliki makna filosofis yang mendalam dan sejalan dengan prinsip Islam. Di antaranya adalah nilai akulturasi budaya dalam Mengambik Tanah, penyucian diri dalam Duduk Penja, semangat persaudaraan Islam dalam Menjara, dan refleksi diri dalam Tabot Tebuang. Dari sudut pandang hukum Islam, ritual Tabot menggambarkan adaptasi praktik ritual yang harmonis dengan tetap berpegang pada rasa hormat dan hidup berdampingan dalam ajaran Islam. Modifikasi simbolik ritual tersebut, seperti menghilangkan unsur-unsur yang dianggap menyinggung para Sahabat Nabi Muhammad SAW, mencerminkan komitmen untuk menjaga persatuan Islam. Meski berasal dari tradisi Syiah, ritual Tabot telah dikontekstualisasikan dan diterima secara luas, termasuk oleh komunitas Sunni, yang menunjukkan keselarasan dengan nilai-nilai yurisprudensi Islam.